RANCANG BANGUN HIDROPONIK TANAMAN PAPRIKA DENGAN DRIP SYSTEM BERBASIS INTERNET OF THINGS - Teguh Purwanto, Kadek; Sukadarmika, Gede; .Wiharta, D.M. (Jurnal SPEKTRUM, 2022)
Technological advances have been utilized in various fields, including in agriculture. The technology that is currently widely used is the Internet of Things (IoT). With this technology, farmers can monitor and control remotely so that their work becomes more efficient and optimal. In this study, a control and monitor system was developed for paprika hydroponics. This system was built using a Rasberry Pi as a data processing center equipped with Arduino uno as an analog data reader and relay control, a DS18B20 sensor as a water temperature reader, a pH 4502C sensor as a water acidity reader, and a TDS/EC sensor as a water nutrient ppm value reader. This system is realized in the form of a prototype system for hydroponic paprika. The system works automatically to monitor and control water temperature, water pH, nutrient ppm value, water level and automatic watering. The system is also equipped with a notification feature so that farmers can obtain information via telegram media such as water temperature, water pH, nutrient ppm value, water level, and watering notifications. This prototype is also equipped with a webcam camera as a feature that functions to detect ripe peppers in terms of fruit color. The camera will detect the color of the peppers, and if the peppers are red, the peppers are categorized as ripe, and farmers will receive notifications via telegram in the form of image data and notifications that ripe peppers have been detected.